Exploring neural changes associated with suicidal ideation and attempts in major depressive disorder: A multimodal study - Juan Deng; Maomao Zhang; Guangxiang Chen; Xiaofei Lu; Xiaotong Cheng; Cheng Qin; Mingyuan Tian; Ke Gong; Kezhi Liu; Jing Chen; Wei Lei (Brain Research Bulletin)
Suicidal ideation (SI) and suicide attempts (SA) are highly prevalent in individuals with major depressive disorder (MDD). To explore the structural and functional neural changes associated with SI and SA, we analyzed multimodal Magnetic Resonance Imaging (MRI) data from 159 participants, including those with MDD with suicide attempts (SA group, n = 34), those with MDD with suicidal ideation but not attempts (SI group, n = 53), those with MDD without suicidal ideation (NSI group, n = 14), and healthy controls (HC, n = 59). Voxel-based morphometry (VBM) analysis was performed to estimate and compare gray matter volume (GMV) across groups. Subsequently, a seed-based resting-state functional connectivity (rsFC) analysis was conducted to explore the functional networks associated with the structural brain changes related to suicidal ideation and suicide attempts. Compared with the HC and NSI groups, the SI group showed decreased GMV in the left dorsolateral prefrontal cortex (DLPFC), insula, fusiform gyrus, right posterior cerebellum, and right middle temporal gyrus. Additionally, when compared to the HC and SI groups, the SA group demonstrated smaller GMV in the right superior medial frontal gyrus (SFGmed), left superior and inferior occipital gyri, and superior temporal gyrus (STG), and right cuneus, but larger GMV in the right STG. Moreover, GMV in the insula, cerebellum posterior lobe, and SFGmed was negatively correlated with the scores of the Beck Scale for Suicide Ideation (BSSI). The rsFC analysis revealed weaker rsFC between the left insula and the left SFG as well as between the bilateral middle frontal orbital gyrus and the right SFGmed and the left middle occipital gyrus, but stronger rsFC of the right cerebellum posterior lobe with the left precentral gyrus and right parahippocampal gyrus among the SI group compared to the NSI group and HCs. Additionally, the SA group demonstrated weaker rsFC between the right cerebellum posterior lobe and the left cerebellum posterior lobe as well as the right lingual gyrus, but stronger rsFC between the right SFGmed and the left middle temporal gyrus and right inferior parietal lobule compared to the SI group. Our results indicate that structural and functional changes related to insula, DLPFC and cerebellum posterior lobe are associated with the generation and escalation of SI in MDD, while the structural and functional changes related to SFGmed and STG play a crucial role in the transformation from SI to SA in MDD.